Time-dependent electron transport through a strongly correlated quantum dot: multiple-probe open-boundary conditions approach - SANVITO, STEFANO (My University, 2013)
We present a time-dependent study of electron transport through a strongly correlated quantum dot. The time-dependent current is obtained with the multiple-probe battery method, while adiabatic lattice density functional theory in the Bethe ansatz local-density approximation to the Hubbard model describes the dot electronic structure. We show that for a certain range of voltages the quantum dot can be driven into a dynamical state characterized by regular current oscillations. This is a manifestation of a recently proposed dynamical picture of Coulomb blockade. Furthermore, we investigate how the various approximations to the electron-electron interaction affect the line-shapes of the Coulomb peaks and the I-V characteristics. We show that the presence of the derivative discontinuity in the approximate exchange-correlation potential leads to significantly different results compared to those obtained at the simpler Hartree level of description. In particular, a negative differential conductance (NDC) in the I-V characteristics is observed at large bias voltages and large Coulomb interaction strengths. We demonstrate that such NDC originates from the combined effect of electron-electron interaction in the dot and the finite bandwidth of the electrodes.
PUBLISHED
Keywords: Physics; Nanoscience & Materials